2016
DOI: 10.1128/aac.01916-15
|View full text |Cite
|
Sign up to set email alerts
|

Antitrypanosomal Activities and Mechanisms of Action of Novel Tetracyclic Iridoids from Morinda lucida Benth

Abstract: Trypanosoma brucei parasites are kinetoplastid protozoa that devastate the health and economic well-being of millions of people in Africa through the disease human African trypanosomiasis (HAT). New chemotherapy has been eagerly awaited due to severe side effects and the drug resistance issues plaguing current drugs. Recently, there has been an emphasis on the use of medicinal plants worldwide. Morinda lucida Benth. is a popular medicinal plant widely distributed in Africa, and several research groups have rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…Regarding the components of mango, although it has been suggested that the most important constituent in mango‐related antiparasitic activity is mangiferin having the C‐glucosyl xanthone structure (Wauthoz & Balde, ), the active component is still unknown. In this regard, we intend to employ the bioassay‐guided fractionation techniques to determine the active components of the promising anti‐ Plasmodium active extracts as in the case of M. lucida (Kwofie et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the components of mango, although it has been suggested that the most important constituent in mango‐related antiparasitic activity is mangiferin having the C‐glucosyl xanthone structure (Wauthoz & Balde, ), the active component is still unknown. In this regard, we intend to employ the bioassay‐guided fractionation techniques to determine the active components of the promising anti‐ Plasmodium active extracts as in the case of M. lucida (Kwofie et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Alamar Blue assay (Alamar Blue®, Life Technologies™, USA) was used to determine the antitrypanosomal and antileishmanial activities of plant extracts. Assays were carried out in a 96‐well plate following manufacturer's instructions with modifications (Kwofie et al, ). Either 1.5 × 10 4 Trypanosoma parasites per well or 1.25 × 10 5 Leishmania parasites per well were seeded with varied concentrations of crude extracts ranging from 0 to 200 μg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there is little commercial interest in the development of new or improved therapeutics for these poor affected populations. [8,9] In a previous work, SA and some derivatives exhibited IC 50 values against Trypanosoma cruzi epimastigotes similar to that of the commercial drug benznidazole (IC 50 about 2 μg/ ml -5.8 μm). [5] Secochiliolide acid (1, SA) is the major secondary metabolite present in the Patagonian endemic shrub Nardophyllum bryoides.…”
Section: Introductionmentioning
confidence: 60%